Pengaruh kepemilikan manajerial, board size, dividen masa lalu dan kesempatan investasi terhadap kebijakan dividen pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia - Dina Patrisia; Hannafika Ihsan (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of managerial ownership, board size, investment opportunities and investment opportunities on dividend policy with proxy payout ratio (DPR), dividend per shares (DPS) and dividend yield (DY) on manufacturing companies listed on the IDX. This research is classified as causative research. The population in this study were all Manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique in this study is using purposive sampling technique with a total sample of 231 companies a year. The data used are secondary data obtained from www.idx.co.id and Indonesia Capital Market Directory. Data analysis method used is multiple regression. The results of multiple regression tests show that past dividends have a positive effect on dividend policy with all dividend policy proxies, subsequently investment opportunities have a positive effect on dividend policy with proxies from the DPR and DPS. While other variables do not affect dividend policy.